Evaluation of loop-mediated isothermal amplification method for efficient detection of the periodontopathic bacteria Porphyromonas gingivalis - Meenaz N. Sangolli; Manohar S. Kugaji; Suman Kumar Ray; Kishore G. Bhat (Wolters Kluwer Medknow Publications, 2024)
Background: Periodontitis is a multifactorial, polymicrobial oral inflammatory illness brought on by oral pathogens. Porphyromonas gingivalis is a Gram-negative, obligatory anaerobic, black-pigmented coccobacillus and is regarded as a primary etiological factor in the progression of periodontitis. Rapid, highly senstitive and specific detection methods are emerging. The present study aimed to evaluate the loop-mediated isothermal amplification (LAMP) technique for efficiently detecting P. gingivalis from subgingival plaque samples of chronic periodontitis patients. Materials and Methods: This study included 50 subgingival plaque samples from patients suffering from chronic periodontitis. The DNA (Deoxyribonucleic acid) was extracted by the "modified proteinase K" method. A set of six primers, targeting the pepO gene of P. gingivalis, was used for conducting LAMP. The amplification was visualized by naked-eye detection and agarose electrophoresis. Conventional polymerase chain reaction (PCR) and real-time qantitative PCR (qPCR) were carried out by targeting the 16SrRNA (16S ribosomal ribonucleic acid) gene of P. gingivalis. Results: The results showed that LAMP detected P. gingivalis in 40 out of 50 samples (80%). Whereas, qPCR and conventional PCR technique detected P. gingivalis in 38 (76%) and 33 (66%) samples respectively. The sensitivity and specificity of the LAMP method were 94.87% and 90.90%, respectively. With qPCR, the sensitivity and specificity were found to be 92.30% and 81.81%, respectively, whereas, with conventional PCR, it was found to be 76.92% and 72.72%, respectively. Conclusion: LAMP is an efficient technique for quick, accurate, and reliable identification of P. gingivalis from subgingival plaque samples. The technique needs to be validated analytically, and further studies can be conducted by taking saliva and/or gingival crevicular fluid samples from periodontitis patients.